THE STATE OF THE POPULATIONS OF NECTAROSCORDUM BULGARICUM IN THE STRICTLY PROTECTED ZONE OF THE “CODRII” RESERVE, REPUBLIC OF MOLDOVA - Natalia JARDAN (Journal of Plant Development)
Nectaroscordum bulgaricum – Honey garlic, a vulnerable species, included in the Red Book of the Republic of Moldova, is territorially protected in the “Codrii” Reserve. The aim of the study was to identify and describe the Honey garlic populations, as a result the trend of the species will be estimated. As a result, 11 populations were identified and described in subplots: 40E, F, K; 41B, J, K; 42H; 46A, E, D and 49E. The geographical coordinates were taken and the map with the location of the identified populations was developed. The state of the populations of Honey garlic in the strictly protected zone of the “Codrii” Reserve was evaluated.